THE ROLE OF COUNSELING GUIDANCE TEACHERS IN MOTIVATING STUDENTS DURING THE COVID-19 PANDEMIC IN MAN KOTAWARINGIN TIMUR - Nor Prasasti Ningsih; Sri Windarti (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2022)
Learning motivation is an important aspect in order to achieve the planned learning goals both inside the school and outside the school. This study aims to determine the actions of BK teachers in providing learning motivation for students at MAN Kotawaringin Timur during the implementation of learning at home due to the Covid-19 pandemic in Indonesia. The research method applied is descriptive qualitative, while the data collection technique is carried out through interviews with the subject writers of guidance and counseling teachers at MAN Kotawaringin Timur. The result of this research is that the role of BK teachers in motivating students during the Covid-19 pandemic is to provide reinforcement to students, provide solutions to student problems, provide character education to students, BK teachers work together with homeroom teachers and subject teachers to communicate to students' problems, difficulties, and obstacles online, provide an understanding of the importance of learning, helps increase students' willingness to do learning, providing encouragement and motivation to learners.